FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DI PERUSAHAAN MANUFAKTUR - Riny, Riny (CV. Era Digital Nusantara, 2024)
This research to determine the impact of capital intensity ratio, size, leverage, independent commissioners, institutional ownership on tax management. This research is a quantitative descriptive studies, with a special criteria sample (purposive sampling), a population of 289, drawn as a sample of 62 companies from the population. The testing method uses SmartPLS, construct model. The test results believe that leverage have effect on tax management, capital intensity ratio; size, independent commissioners, institutional ownership have no effect on tax management in manufacturing companies.